Analysis of intravenous sedation for dental treatment in elderly patients with severe dementia-a retrospective cohort study of a Japanese population - Hitomi Nishizaki; Yoshinari Morimoto; Megumi Hayashi; Takatoshi Iida (Elsevier, 2021)
Background/purpose: Patients with severe dementia require intravenous sedation during dental treatment. However, few reports have compared the outcomes of intravenous sedation management among sedatives. Intravenous sedation in the elderly with severe dementia undergoing dental treatment was evaluated retrospectively. Materials and methods: Patients' characteristics and type of dementia were obtained from medical records. Midazolam (MID), dexmedetomidine (DEX), and propofol (PRO) were administered as sedatives. The systolic blood pressure (SBP), heart rate (HR), SpO2, bispectral index (BIS) values and complications were evaluated. Results: Nineteen patients with severe dementia who underwent 62 instances of sedation were included. There was no difference in patient background between sedatives. The sedation time and permission time to return home were significantly longer in DEX than in MID or PRO group. Half the usual dose in MID and lower limits of the routine dose was effective in DEX and PRO. HR was significantly lower in DEX group. There were 3 cases with airway obstruction requiring nasopharyngeal airway and 4 cases of apnea when MID was administered. Two cases of Cheyne-Stokes-like respiration when MID or DEX was administered. SpO2 <94% was found in 22 cases (35%) irrespective of the sedative. A patient with dementia with Lewy bodies had experienced hallucinations during the recovery period after sedation when MID or DEX was administered. The BIS value of ≤80 was noted during complications. Conclusion: Intravenous sedation for dental treatment in the elderly with severe dementia, needs a dose titration. All sedatives had respiratory-related complications which mandate close monitoring.